Application of the CRISPR/Cas9 Gene-editing System and Its Participation in Plant and Medical Science - Angon*, Prodipto Bishnu; Ummya Habiba (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
The long-term goal of scientists and breeders is to study the efficacy of a gene, as well as to use it in the development of human life and in the development of improved quality and varieties of crops. CRISPR/Cas9, a gene-editing tool, has already uncovered a wide range of applications in areas such as human disease diagnosis and the development of new crop varieties. This review provides basic ideas about CRISPR/Cas9 as well as its importance in the current context. CRISPR/Cas9 editing tool has more contributions to plant science than medical science. As a mature cutting-edge biotechnological technique, CRISPR/Cas9 has been applied in a variety of crop related research and development areas including disease resistance, plant development, abiotic tolerance, morphological development, secondary metabolism, and fiber formation. Lastly, some of the limitations of this system have been mentioned, and aspects of more research in the future have been suggested. Through this review, readers will better be able to understand the CRISPR/Cas9 genome editing system and will be familiar with much of the research that has occurred from the past to the present in a range of science fields. Keywords: CRISPR; Cas9; crop development; gene editing; genetical disorder; medical science; human diseases *Corresponding author: Tel.: (+880) 1717697088 E-mail: angonbishnubau@gmail.com